Multi-Skilled Worker Matching Method Considering The Changes of Serus in The Seru Production System - Huang, Kunyuan; Jiang, Yanping; Zhang, Yangxin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
In the seru production system (SPS), matching multi-skilled workers and serus is a crucial problem. In this paper, a multi-skilled worker matching method in SPS considering the changes of serus is proposed. It can be used to generate the initial matching scheme for multi-skilled workers and serus before the production begins, and to adjust the matching scheme under the changes of serus caused by the changes of production tasks during production. Firstly, according to the preference information of multi-skilled workers and processes in the SPS, the satisfaction degree calculation methods of multi-skilled workers and processes in the SPS are proposed. Furthermore, a multi-objective programming model for matching multi-skilled workers and serus is constructed. Meanwhile, based on the classical multi-objective immune algorithm (MOIA), an improved multi-objective immune algorithm (IMOIA) is designed to solve the model. The experimental results demonstrate that IMOIA has advantages over other algorithms in set size, dominance, convergence, and distribution uniformity of Pareto solutions. Finally, the effects of different matching scheme adjustment methods and different algorithms are compared, and sensitivity analyses are carried out.